Adubação com fontes de silício via solo na qualidade de sementes de trigo sob estresse salino - Castellanos, César Iván Suárez (2014)
Wheat (Triticum aestivum L.) is a cereal of the Poaceae family, which is used as feedstock in the manufacture of various foods. It is the most produced in the world and the fourth largest cereal crop in Brazil. It is estimated that 50% of irrigated areas in the world have problems caused by salinity decreasing crop yields. Silicon has been used to reduce stress caused by salts in plants. The objective of this study was to evaluate the effect of fertilization with two silicon sources on the quality of wheat seeds under salt stress. Two experiments were performed, one using a silicon source kaolin and other rice husk ash. Seeds of wheat cultivar Quartzo were sown in 10L buckets containing soil, which was corrected according to soil analysis and technical advice on the culture. Silicon was incorporated at the time of seeding, increasing doses of both sources being applied: 0 (control), 1.000, 2.000 and 3.000 Kg ha-1. To simulate the salinity irrigation was performed with NaCl solutions throughout the crop cycle, at concentrations of 0 (control), 8 and 16 mM. The experiment was conducted in a completely randomized design with a 3x4 factorial design with four replications. Agronomic traits and seed quality were evaluated. The results showed that the application of 3.000 Kg ha-1 of silicon in the form kaolin increased the rate of germination of seeds harvested when the plants are not exposed to salt stress. The application of silicon in the soil increases the weight of a thousand seeds in conditions of saline stress or not. The use of rice husk ash as a source of silicon to a dose of 2,000 Kg ha-1, stimulates the development of agronomic traits in wheat plants. Agronomic and physiological seed quality is viewed differently influenced by the sources of silicon used.